Discipline and promote: Building infrastructure and managing algorithms in a "structured journalism" project by professional fact-checking groups. (February 2020) - Graves, Lucas; Anderson, CW
News organizations have adapted in various ways to a digital media environment dominated by algorithmic gatekeepers such as search engines and social networks. This article dissects a campaign to actively shape that environment led by professional fact-checking organizations. We trace the development of the Share the Facts "widget, " a device designed to give fact-checks greater purchase in algorithmically governed media networks by driving adoption of a new data standard called ClaimReview. We show how "structured journalism" gave journalists a language for the social and technical challenges involved, and how this infrastructural technology mediates between fact-checkers, audiences, and platform companies. We argue that this standard-setting initiative exhibits both promotional and disciplining facets, offering greater distribution and impact to journalists while also defining their work in specific ways. Crucially, in this case, this disciplining influence reflects internal professional-institutional agendas in an emerging subfield of journalism as much as the demands of platform companies.